TAXONOMICAL STUDY FOR THE SPECIES CHENOPODIUM ALBUM L. AND CHENOPODIASTRUM MURALE L. BELONG TO AMARANTHACE (CHENOPODIACEAE ) AT BAGHDAD - Zainab Adel Ahmed; Sukeyna Abaas Aliwy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The current research dealt with a comparative taxonomic study of the two types Chenopodium album L. and Chenopodiastrum murale L. at Baghdad , This research was included a cytological study by calculating the chromosome number by sequence n=27,9. and studying the micro-morphological characteristics of the seeds and fruits of the two types, in addition to the surface covering in the leaf part. All phenotypic characteristics of the seeds were studied by scanning electron microscope (SEM) and Light microscope (LM) in terms of shape, colour, dimensions Seed size were measured by the program digmizer , as well as the configuration of the seeds surface , The seeds of Ch.album were distinguished by their dark-black color, while the seeds of the other type were greenish-brown, seeds in addition to the fruits, helped to isolate and classify the two types. The surface covering results showed a variation in terms of density and distribution method on the leaf surface , and the presence of glandular-bladder and a glandular hairs was recorded in Ch.album, while for Ch.murale hairs of the a glandular type were observed. It is worth noting that all the results obtained in this research are presented for the first time in Iraq.